2014
DOI: 10.1310/hpj4901-32
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antimicrobial Competencies and Training for Staff Hospital Pharmacists

Abstract: Antimicrobial stewardship is an important component in health care outcomes of all patients. Many institutions are seeking the best methods to incorporate antimicrobial stewardship strategies into their hospitals including pharmacy services. Multiple factors should be considered when beginning or expanding an antimicrobial stewardship program. The purpose of this article is to discuss the development of basic antibiotic competencies and training for staff pharmacists in a community hospital. The article includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Similarly, AMS has been implemented in the majority of European countries in order to reduce the abuse and misuse of antimicrobials, the associated risk of resistance and adverse events [21] expenditure, the prevalence of resistant pathogens [47,48], and improve clinical outcomes [47,49]. In our study, 87.8% pharmacist agreed that suitable training should be offered to pharmacists on the appropriate use of antimicrobials, similar with the findings of Crader M et al that for all pharmacists in the hospital setting, antimicrobial steward programs should be initiated, and antibiotic competency and training should be offered [45,50]. Similarly, Dellit TH et al stated that pharmacists should have infectious disease training to work in hospitals in order to optimize antibiotic stewardship [51].…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, AMS has been implemented in the majority of European countries in order to reduce the abuse and misuse of antimicrobials, the associated risk of resistance and adverse events [21] expenditure, the prevalence of resistant pathogens [47,48], and improve clinical outcomes [47,49]. In our study, 87.8% pharmacist agreed that suitable training should be offered to pharmacists on the appropriate use of antimicrobials, similar with the findings of Crader M et al that for all pharmacists in the hospital setting, antimicrobial steward programs should be initiated, and antibiotic competency and training should be offered [45,50]. Similarly, Dellit TH et al stated that pharmacists should have infectious disease training to work in hospitals in order to optimize antibiotic stewardship [51].…”
Section: Discussionsupporting
confidence: 84%
“…There is limited research evaluating the impact of educational interventions or comparing different interventions to improve hospital pharmacists’ knowledge and skills in AMS. One study conducted in the United States described the development and evaluation of an educational and training program targeted at pharmacists in a community hospital without an ID/AMS pharmacist on site [ 28 ]. Multiple didactic and active educational strategies (lectures, small group sessions and online learning) were employed to teach AMS interventions such as intravenous-to-oral switch, and dose-adjustment based on renal function.…”
Section: Discussionmentioning
confidence: 99%
“…3 Hospital pharmacists' perceived usefulness of different modes of education delivery relating to antimicrobial stewardship interventions *p ≤ 0.01 when comparing hospital pharmacists' perceived usefulness of e-learning and didactic programs to other more interactive modes for responses categorized as 'very useful/useful'. There was no difference between e-learning and didactic programs community hospital without an ID/AMS pharmacist on site [28]. Multiple didactic and active educational strategies (lectures, small group sessions and online learning) were employed to teach AMS interventions such as intravenous-to-oral switch, and dose-adjustment based on renal function.…”
Section: Discussionmentioning
confidence: 99%
“…One study focused on improving antimicrobial stewardship competency in 17 hospital pharmacists. 8 This study found improvements in knowledge after completion of the program, although changes in self-efficacy were not measured. The program was delivered over a 4-month period and was primarily delivered through a lecture-based format.…”
Section: Discussionmentioning
confidence: 67%
“…[4][5][6] Limited literature within the hospital pharmacy setting exists evaluating CBA programs, and mostly focuses on training programs for specific clinical tasks. 7,8 Therefore, it is unclear whether CBA programs are an effective method to evaluate pharmacist's knowledge, clinical skills, and confidence within the hospital setting.…”
Section: Introductionmentioning
confidence: 99%